Fungsi Heterotopia Masjid Al Lathiif dalam Aktivitas Dakwah di Kota Bandung - Dede Irawan; Dede Lukman (Institut Agama Islam Persis Bandung, 2026)
This article examines Al-Lathiif Mosque in Bandung as a heterotopic space that reflects the intersection of the sacred and the profane dimensions within urban society. Using a descriptive qualitative approach, the study explores how the mosque functions not only as a place of worship but also as a social, psychological, and cultural arena that responds to the complex needs of urban residents. The findings reveal that Al-Lathiif Mosque serves as an alternative space that offers inner tranquility, a slower rhythm of time, and an atmosphere that alleviates the pressures of urban life. At the same time, the mosque has evolved into an inclusive community space where diverse groups interact beyond rigid ideological boundaries. The mosque becomes a meeting point across identities while symbolizing reconciliation between tradition and modernity. These dynamics affirm that Foucault’s concept of heterotopia remains relevant for understanding the role of urban mosques as spaces that reconfigure the spiritual, social, and cultural experiences of urban communities.